Older Adults Benefit from Symmetry, but Not Semantic Availability, in Visual Working Memory - Hamilton, Colin J.; Brown, Louise A.; Rossi-Arnaud, Clelia (Frontiers in Psychology, 2018)
Visual working memory exhibits age effects that are amongst the largest observed in the cognitive aging literature. In this research we investigated whether or not older adults can benefit from visual symmetry and semantic availability, as young adults typically do. Visual matrix pattern tasks varied in terms of the perceptual factor of symmetry (Experiment 1), as well as the availability of visual semantics, or long-term memory (LTM; Experiment 2). In Experiment 1, within a visual memory span protocol, four matrix pattern sets were employed with discrete symmetry characteristics; random, vertical, horizontal, and diagonal symmetry. Encoding time was 3 seconds with a 1 second maintenance interval. The findings indicated a significant difference in span level across age groups for all of the symmetry variants. More importantly, both younger and older adults could take advantage of symmetry in the matrix array in order to significantly improve task performance. In Experiment 2, two visual matrix task sets were used, with visual arrays of either low or high semantic availability (i.e., they contained stimuli with recognisable shapes that allow for LTM support). Encoding duration was 3 seconds with immediate recall. Here, the older adult sample was significantly impaired in span performance with both variants of the task. However, only the younger adult participants could take advantage of visual semantics. These findings show that, in the context of overall impairment in individual task performance, older adults remain capable of employing the perceptual cue of symmetry in order to improve visual working memory task performance. However, they appear less able, within this protocol, to recruit visual semantics in order to scaffold performance.